Macroalgae Diversity in Seagrass Ecosystem at Ranowangko Dua Village Beach - Rantung, Live Clarisa Ivon; Ogi, Nova Laurin Isye Mourein; Roring, Verawati Ida Yani; Rampengan, Mercy Maggy Franky (Jurnal Ilmiah Platax, 2024)
This research aims to provide information on the types, and diversity of macroalgae in seagrass ecosystems and water conditions in the waters of Ranowangko Dua Village Beach, Kombi District, Minahasa Regency. Observations of macroalgae in seagrass ecosystems were carried out using the quadrant transect method (1x1m) along 100 meters with an observation distance of every 10 meters per quadrant using 3 transect lines with a distance of 10 meters. The results found 12 species of macroalgae namely Halimeda Macroloba, Ulva intestinalis, Caulerpa Lentillifera, Neomeris Annulata, Halimeda Incrassata, Codium Arabicum, Turbinaria Ornata, Padina Minor, Acanthophora Spicifera, Amphiroa Fragillisima, Galaxaura Rugosa, and Mastophora Rosea. The diversity values of transects 1, 2, and 3 are 1.745; 1.378, and 1.294, respectively, included in the medium category. The absolute density value was highest in transect 2 (12.1), and lowest in transect 3 (7.5). The uniformity values of transects 1, 2, and 3 were 0.702; 0.555, and 0.521, respectively, including moderate (0.50 and less than 0.75). The dominance values of transects 1, 2, and 3 are 0.228; 0.348, and 0.362 respectively, which fall into the stable category or there is no dominating species. The results of physical and chemical parameters show the temperature value of 31.14°C, pH 8.99 is stable, and Dissolved Oxygen 7.62 mg/l is not polluted. In contrast, the salinity value of 35.14 ppt is not optimal, the brightness is in the low category of 0.38 m, and the turbidity value of 103 NTU is in the high category. Keywords: Seagrass ecosystem, macroalgae, ecological index, physical parameters, chemical parameters. Abstrak Penelitian ini bertujuan untuk memberikan informasi tentang jenis, keanekaragaman makroalga pada ekosistem padang lamun dan kondisi air di perairan Pantai Desa Ranowangko Dua Kecamatan Kombi Kabupaten Minahasa. Pengamatan makroalga pada ekosistem lamun dilakukan dengan metode transek kuadran (1x1m) sepanjang 100 meter dengan jarak pengamatan setiap 10 meter per kuadran menggunakan 3 line transek dengan jarak 10 meter. Hasil yang ditemukan 12 species makroalga yaitu Halimeda Macroloba, Ulva Intestinalis, Caulerpa Lentillifera, Neomeris Annulata, Halimeda Incrassata, Codium Arabicum, Turbinaria Ornata, Padina Minor, Acanthophora Spicifera, Amphiroa Fragillisima, Galaxaura Rugosa, dan Mastophora Rosea. Nilai keanekaragaman transek 1, 2 dan 3 masing-masing 1,745; 1,378 dan 1,294 termasuk dalam kategori sedang. Nilai Kepadatan mutlak tertinggi pada transek 2 (12,1), dan terendah pada transek 3 (7,5). Nilai keseragaman transek 1, 2 dan 3 masing-masing 0,702; 0,555 dan 0,521 termasuk sedang (0,50 dan kurang 0,75). Nilai dominansi transek 1, 2 dan 3 masing-masing 0,228; 0,348 dan 0,362 dimana masuk dalam kategori stabil atau tidak ada jenis yang mendominasi. Hasil parameter fisik dan kimia menunjukkan nilai suhu 31,14°C, pH 8,99 tergolong stabil, Oksigen Terlarut 7,62 mg/l tidak tercemar, sedangkan nilai salinitas 35,14 ppt tidak optimal, kecerahan dalam kategori rendah 0,38 m, dan nilai kekeruhan 103 NTU dalam kategori tinggi. Kata kunci : Ekosistem lamun, makroalga, indeks ekologi, parameter fisik, parameter kimia